A study of prescription pattern in the drug therapy of ear, nose, and throat infections at a tertiary care hospital in Mangalore - Bhat, G. M. Nitasha; Holla, Rajendra; Kamath P., Shrinath D. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Diseases of the ear, nose, and throat (ENT) constitute among the most common causes of hospital visits worldwide and account for most of the antibiotics prescribed and used. They are responsible for significant school and work absenteeism and have generated 94.6 disability-adjusted life years lost worldwide. Due to the high incidence of these diseases and the different varieties of drugs in use, it becomes imperative for us to know the present prescribing patterns, so that appropriate adjustments can be made for the benefit of patients. Methods: Over a period of 1-year, the outpatient department (OPD) records of 608 patients with ENT infections, reporting to the ENT OPD of Justice K S Hegde Charitable Hospital, Deralakatte, Mangalore, were scrutinized and the data collected in a specially designed proforma. Descriptive analysis of the data was done. Results: Of the total 608 prescriptions analyzed, 309 (50.8%) belonged to male patients and 299 (49.2%) belonged to female patients. Highest numbers of patients were in the age group of 16-25 years (29.44%). The most common diseases reported were chronic suppurative otitis media (19.24%), followed by otitis externa (13.49%) and furunculosis (9.87%). Average number of drugs per prescription was found to be 3.0. Oral antibiotics were prescribed to 540 patients (88.81%). Most common antibiotics prescribed were amoxicillin-clavulanate (53%), levofloxacin (17%), and cefixime (14%). Antihistamines were prescribed in 52.47% prescriptions, and non-steroidal anti-inflammatory drugs were prescribed to 298 patients (49.01%). Conclusion: This study shows that the diseases were treated rationally in accordance with the standard guidelines of therapy.